A STUDY OF STUDENTS’ PERCEPTIONS OF THE PBL ENVIRONMENT AND LEARNING MOTIVATION IN THE EFFECTIVE COMMUNICATION CLASS AMONG UNDERGRADUATES OF FACULTY OF TECHNOLOGY MANAGEMENT, BUSINESS AND ENTREPRENEURSHIP, UNIVERSITI TUN HUSSEIN ONN MALAYSIA (UTHM) - Abdul Kadir, Zulida; Abdullah, Nor Hazana; Mohd Salleh, Berhannuddin (Journal of Techno-Social, 2013)
Problem based learning (PBL) is claimed to be one of the best methods for interactive learning, and more effective than the traditional teaching and learning methods. However, there is still a limited empirical evidence of the effectiveness of PBL across various courses and learning disciplines. The aim of this study was to identify students’ perceptions of learning environment and motivation in Effective Communication classes using a PBL approach. Twenty five students participated in this single case study. Students were given four treatments and answered questionnaires in gauging their perception and motivation on the PBL approach to learning. Results indicated that these students who attended PBL classes have a positive perception of learning environment after attending the course. However, there is no significant difference on students’ motivation at the beginning and at the end of the course.